Existing at the Center for Documentation Unit of the National University Library Documents - Fernández Aguilar, Mayra (1981)
Publication of summaries librarians to contribute to the knowledge and exchange of literature that takes place in the school of bibliotecología. The work has been elaborated by students in his course of documentation.